The Influence of Work-Life Balance and Compensation on Employee Job Satisfaction at PT. XYZ (A Study on The Internal Monitoring Division, Corporate Secretaries, and Quality Assurance and Regulatory Division) - Pratama, Al Dharma; Saragih, Romat (Universitas Pamulang, 2023)
This study is focused on assessing the level of employee satisfaction at PT XYZ, particularly in the three divisions, namely internal unit supervisors, company secretaries, and quality assurance & regulation. This study aimed to investigate and assess how Work-life balance and Compensation impact the employees' level of Job Satisfaction in the three divisions. In this study, a quantitative method was employed, utilizing a fully saturated sample comprising 100 respondents. Data analysis was conducted through descriptive analysis and multiple linear regression using the SPSS 26 application for windows. The findings of this descriptive study indicate that Work-life balance falls into the good category, compensation is rated as very good, and job satisfaction is also very good. Furthermore, In this study, the findings indicate that both Work-life balance and compensation have a significant and simultaneous impact on job satisfaction.